(untitled) (Research, Society and Development, 2020)
Introduction: Osteomas are proliferations of bone tissue, a benign neoplasm clinically consisting of a well-defined mass that can be sessile or pediculated, asymptomatic and which, depending on its location and size, can cause damage to adjacent structures, besides functional and aesthetic changes. Objective: report a case of periosteal compact osteoma in the mandibular region. Case Report: Patient N.B, female, 33 years old, was seen at the Hospital da face (Recife – PE) complaining of an increase in hardened volume on palpation in the left submandibular region. On physical examination, he presented a hardened, sessile and painless lesion, with an evolution time of approximately 1 year. After clinical examination, computadorized tomography was requested for further evaluation. The tomographic image showed the presence of a hyperdense lesion in the region of the left mandibular body. Due to the appearance of the lesion, surgical excision was chosen through submandibular extra-oral access. After excision, the specimen was sent to a histopathological study that identified the lesion as a compact osteoma. Discussion: Anamnesis and physical examination are of paramount importance for the diagnosis of osteoma, as it is an asymptomatic pathology. The initial treatment approach is monitoring, if the osteoma causes functional or aesthetic disorders, the treatment chosen is surgical excision. Conclusion: Osteoma is a benign neoplasm which in some cases, surgical intervention is necessary due to aesthetic and functional impairment, as reported in the present case.